Densidade populacional de fungos e o potencial biotecnológico em área sob restauração florestal no ecótono cerrado / Amazônia - Kavasaki, Kaynara Fabíola Lima (2015)
The Cerrado and Amazon transition area includes part of biomes with incalculable biodiversity value, however, this area are inside of expansion from agricultural frontier, which may cause negative environmental impacts. Thus, there is a growing demand for alternatives aimed to reduce land degradation through forest restoration. In this sense, evaluate the microbial community from soil will contribute to understand the impact of these techniques on the soil quality as well bioprospect microorganisms with biotechnological potential as biocontrol of plant pathogens. The objective of this study was to quantify and bioprospect fungi antagonistic to Rhizoctonia solani and Fusarium oxysporum, present in a soil under forest restoration and in a native-forest area. Ten forest-restoration treatments and a native-forest area were evaluated. Fungal isolation and evaluations of antagonism were performed on PDA medium. Antagonist isolates were identified by sequencing rDNA region ITS1-58S-ITS2. When the amount of fungi present was evaluated, the treatments did not differ from each other in their same year of collection, only when compared with the native forest and between years. Of the evaluated isolates, 23 showed antagonistic potential against the studied plant pathogens. Of the ten evaluated treatments, T3 (broadcast seeding of native species/green fertilizers) and the native forests did not show any antagonistic isolate. After taxonomic identification, the isolates were classified as belonging to four genera: Talaromyces, Aspergillus, Taifanglania, and Beauveria. The results indicate the microbiological parameters of the studied area should be evaluated continuously, as they may help determine strategies regarding the forest restoration treatments, contributing to the preservation/restoration of degraded areas and maintenance of the microbial biodiversity.